2015
DOI: 10.1016/j.nbd.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Seizure-related regulation of GABAA receptors in spontaneously epileptic rats

Abstract: In this study, we analyzed the impact that spontaneous seizures might have on the plasma membrane expression, composition and function of GABAA receptors (GABAARs). For this, tissue of chronically epileptic rats was collected within 3 hours of seizure occurrence (≤3 hours group) or at least 24 hours after seizure occurrence (≥24 hours group). A retrospective analysis of seizure frequency revealed that selecting animals on the bases of seizure proximity also grouped animals in terms of overall seizure burden wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 50 publications
2
27
0
2
Order By: Relevance
“…It has been proposed since 1958 (Jung et al, 1958) that, seizures occur as a result of altered excitatory/inhibitory balance; therefore, an altered GABA A receptor (R) function may contribute to epileptogenesis (Scharfman and Brooks-Kayal, 2014;González et al, 2015). In line with this hypothesis, we have shown that GABA A -Rs in the epileptic brain, when repetitively activated, display a marked current desensitization known as rundown (Ragozzino et al, 2005;Palma et al, 2007), thereby contributing to the GABAergic impairment in epilepsy.…”
Section: Introductionsupporting
confidence: 80%
“…It has been proposed since 1958 (Jung et al, 1958) that, seizures occur as a result of altered excitatory/inhibitory balance; therefore, an altered GABA A receptor (R) function may contribute to epileptogenesis (Scharfman and Brooks-Kayal, 2014;González et al, 2015). In line with this hypothesis, we have shown that GABA A -Rs in the epileptic brain, when repetitively activated, display a marked current desensitization known as rundown (Ragozzino et al, 2005;Palma et al, 2007), thereby contributing to the GABAergic impairment in epilepsy.…”
Section: Introductionsupporting
confidence: 80%
“…The methods described here are similar to those described elsewhere, for further details please refer to our previous reports [12, 13]. Samples were isolated from animals described in the above-mentioned studies and repurposed for the analysis of KCC2 and NKCC1 immunoreactivity.…”
Section: Methodsmentioning
confidence: 99%
“…Rats were injected intraperitoneally with scopolamine methyl nitrate (1 mg/kg) 30 minutes before administration of pilocarpine hydrochloride (385 mg/kg), as previously described [4, 12, 13, 27]. Diazepam (6 mg/kg; Hospira, Lake Forest, IL) was administered to stop seizure progression.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations